Novel allylic phosphonium salts in free radical accelerated cationic polymerization - Gupta, Mukesh Kumar; Singh, Raj Pal (Polymer Bulletin, 2009)
In the present study, the synthesis and evaluation of novel allylic phosphonium salts as addition fragmentation agents in combination of conventional (photo-/thermal) free radical source for cationic polymerization are described. The amide based allylic phosphonium salts, namely 2-(N, N-dimethylcaboxy-propenyl) triphenylphosphonium hexafluoroantimonate (DMTPH) and 2-(morpholinocarboxy-propenyl) triphenyl phosphonium hexafluoroantimonate (MTPH) were synthesized and characterized. The thermal and photo-latency of these salts was examined with and without free radical sources in bulk polymerization of cyclohexene oxide (CHO) salts at 70 A degrees C and lambda > 290 nm irradiation, respectively. In presence of thermal free radical source, the order of activity was observed as PAT > BPO > AIBN. The order of activity of free radical sources on photopolymerization was found to be benzoin > benzophenone > TMDPO. In addition, photopolymerization of other cationically polymerizable monomers (such as n-butyl vinyl ether, isobutyl vinyl ether, N-vinyl carbazole and glycidyl phenyl ether) was also examined at lambda > 290 nm irradiation. It is concluded that the rate of cationic polymerization can be accelerated using novel phosphonium salts with combination of free radical sources, by both thermal and photochemical mode.
Keywords: Addition fragmentation agent; Cationic polymerization; Initiator; phosphonium salt; Photopolymerization

Novel dibenzocycloheptenyl phosphonium salts as thermolatent initiator in cationic polymerization - Gupta, Mukesh Kumar; Singh, Raj Pal (Journal of Applied Polymer Science, 2009)
In this study, novel thermolatent cationic initiators based on dibenzocycloheptenyl phosphonium salts (1a, 1b, 1c, 1d, 2a, and 3a) were synthesized and their efficiency was examined in bulk polymerization of glycidyl phenyl ether (GPE). The polymerization of GPE was performed with 1 mol % of dibenzocycloheptenyl triphenylphosphonium salts (1a-1d) with different counter anions (SbF(6)(-), PF(6)(-), AsF(6)(-), and BF(4)(-)) at 25-200 degrees C for 1 h. The order of initiator activity was found as 1a > 1d > 1b > 1c. To examine the effect of phosphine moiety, the activity of la was compared with dibenzocycloheptenyl-tri-n-butylphosphonium hexafluoroantimonate (2a). The order of initiator activity was observed as 1a > 2a. The initiator activity of la was compared with that of 10,11-dihydro-dibenzocycloheptenyltriphenylphosphonium hexafluoroantimonate (3a) to understand the effect of extended conjugation in dibenzocycloheptenyl ring. In general, with the increase in the polymerization temperature, conversion (%) also increases. The solubility of initiators in various solvents and epoxy monomers was also examined. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 3707-3713, 2009
Keywords: Cationic polymerization; glycidyl phenyl ether; initiators; phosphonium salt; thermolatent